HEALTH EFFECTS OF CHILDRENS OF ALCOHOLICS-THE ROLE OF SELFESTEEM: A COMMUNITY BASED ANALYSIS - GENESTA MARY GYSEL,; PARAMANANDAM,; ARUN TIPANDJAN, (International Journal of Pharma and Bio Sciences, 2015)
The purpose of the study was to investigate the health effects of children of alcoholics and the role of self-esteem. A sample of 400 COAs (Male = 201; Female = 199) was identified with the help of community workers using a snowball sampling technique by audit questionnaire. The result of the study showed that the health effects of COA had a significant negative correlation with the level of self-esteem. When the comparison was made on the basis of age, the age groups between 13-14 years were found to be significant with self-esteem. The major findings of the study reveals that emotional aspect is negatively associated with the financial support of COA and positively associated with effect/illness due to alcohol dependence and Child abuse.There was a negative correlation found between health effects and self-esteem. The study, therefore, concluded that the parental alcohol problem increases the health effects and decreases self-esteem of their children. It is recommended that effective guidance and counselling should be offered to assist the affected students in learning institutions.